Role of Early Elective Cholecystectomy in Acute Mild-To-Moderate Biliary Pancreatitis - Siddique, Muhammad Umar; Wattoo, Nasir Mehmud; Hira; Khan, Tayyaba Mushtaq; Muhammad Naeem; Adil Maqbool (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare the outcomes of early versus delayed laparoscopic cholecystectomy (LC) in patients with mild/moderate acute biliary pancreatitis (ABP).Study Design: Prospective comparative study.Place and Duration of Study: General Surgery Department of Pak-Emirates Military Hospital, Rawalpindi, Pakistan, from Jun 23 to Feb 24.Methodology: The target population included patients who were diagnosed with mild/moderate ABP. 138 participants were distributed equally into two groups:(1) Early LC Group (2) Delayed LC Group. Both groups were compared in terms of operation timing, operative difficulty, intra/post-operative complications, conversion to open cholecystectomy, mortality, total length of stay (LOS) in the hospital, and recurrent biliary events (RBEs).Results:  Mean LOS (days)in Early LC Group was 6.5±1.1 and in the Delayed LC Group was 9.7±1.8(p-value